Efforts to Improve Student Learning Outcomes on the Diversity of Living Creatures in My Environment With a Problem Based Learning Model for Class IV State Primary School 020273 Binjai Utara - Garnasih, Inggid; Ratnasari, Yuni; Hidayat, Hidayat; Sukmawarti, Sukmawarti (Pusdikra-Publishing.com, 2024)
This research aims to improve learning outcomes for Natural Sciences (Science) in class IV of SD Negeri 020273 North Binjai. The low student learning outcomes in Natural Sciences (Science) subjects led to this research being carried out. In the classroom, this research uses problem-based learning (PBL) strategies. The research subjects were fifteen fourth grade students at SD Negeri 020273 North Binjai. The purpose of this research is to provide the results of my use of image media and Problem Based Learning (PBL) methodology to study the diversity of animals that inhabit my area. After giving students a five-question comprehension test, researchers gathered information about their learning goals. Based on the research results, an average of 47% of students in cycle I and 80% of students in cycle II met the KKM. To improve the learning outcomes of class IV Natural Sciences (IPA) students which include the diversity of living creatures around me, this learning completeness value was created. Improving student learning outcomes is the goal of initiatives that apply the problem-based learning (PBL) paradigm. Because scientific research is taught through lectures, researchers often choose this approach.